2009
DOI: 10.7763/ijcte.2009.v1.54
|View full text |Cite
|
Sign up to set email alerts
|

Performance Evaluation of Symmetric Encryption Algorithms on Power Consumption for Wireless Devices

Abstract: s the popularity of wireless networks increases, so does the need to protect them. Encryption algorithms play a main role in information security systems. On the other side, those algorithms consume a significant amount of computing resources such as CPU time, memory, and battery power. This paper illustrates the key concepts of security, wireless networks, and security over wireless networks. Wireless security is demonstrated by applying the common security standards like (802.11 WEP and 802.11i WPA,WPA2) and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
57
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 67 publications
(60 citation statements)
references
References 5 publications
0
57
0
Order By: Relevance
“…However, a balance between encryption/decryption efforts is hard to find when we talk about "classic" encryption methods. Symmetric encryption has the advantage of simplicity but it is more exposed to "brute force" attacks [4], [10]. Encryption based on public and private keys is more robust but it complicates the architecture of the communication system and raises the amount of computational resources required [4], [10].…”
Section: Related Workmentioning
confidence: 99%
“…However, a balance between encryption/decryption efforts is hard to find when we talk about "classic" encryption methods. Symmetric encryption has the advantage of simplicity but it is more exposed to "brute force" attacks [4], [10]. Encryption based on public and private keys is more robust but it complicates the architecture of the communication system and raises the amount of computational resources required [4], [10].…”
Section: Related Workmentioning
confidence: 99%
“…Also, although long key lengths provide more protection, they are more computationally intensive, and may strain the capabilities of computer processors. A performance evaluation reveals that going from 128 bits key to 192 bits key causes increase in power and time consumption by 8% and 256 bits key causes an increase of 16% [8]. So we propose use of industry standard high grade Advanced Encryption Standard (AES) symmetric encryption algorithm with key length of 128-bits and Diffie Hellman Algorithm for this purpose.…”
Section: Data Security Modelmentioning
confidence: 99%
“…Also, although long key lengths provide more protection, they are more computationally intensive, and may strain the capabilities of computer processors. A performance evaluation reveals that going from 128 bits key to 192 bits key causes increase in power and time consumption by 8% and 256 bits key causes an increase of 16% [8]. So we propose use of industrystandard high grade Advanced Encryption Standard (AES) symmetric encryption algorithm with key length of 128-bits for this purpose.…”
Section: Security Implemention On Cloud 41 Data Security Modelmentioning
confidence: 99%
“…Another performance evaluation reveals that AES has an advantage over algorithms-3DES, DES and RC2 in terms of execution time (in milliseconds) with different packet size and throughput (Megabyte/Sec) for encryption as well as decryption. Also in the case of changing data type such as image instead of text, it has been found that AES has advantage over RC2, RC6 and Blowfish in terms of time consumption [8].…”
Section: Comparing Aes With Other Algorithmsmentioning
confidence: 99%